2018
DOI: 10.1530/jme-17-0153
|View full text |Cite
|
Sign up to set email alerts
|

Sorcin is involved during embryo implantation via activating VEGF/PI3K/Akt pathway in mice

Abstract: Our earlier studies have demonstrated the cyclic variation and also the altered expression of sorcin in endometrium during early-to-mid-secretory phase transition in women with unexplained infertility. The current study was undertaken to establish the functional role of sorcin in endometrial receptivity in mice. Results indicated that sorcin was highly expressed during the window of implantation in mice and functional blockage of sorcin caused significant reduction in number of implanted blastocyst. The recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Sorcin increases ABCB1 expression by stimulating CREB1 phosphorylation by PKA, and binding of activated CREB1 to the cAMP response element (CRE) in the −716-−709 bp of the promoter of the ABCB1 gene [34]. Sorcin silencing was also shown to inhibit ABCB1 by suppressing ERK and Akt [76].…”
Section: Sorcin Expression and Abcb1 Expression Are Linkedmentioning
confidence: 99%
See 2 more Smart Citations
“…Sorcin increases ABCB1 expression by stimulating CREB1 phosphorylation by PKA, and binding of activated CREB1 to the cAMP response element (CRE) in the −716-−709 bp of the promoter of the ABCB1 gene [34]. Sorcin silencing was also shown to inhibit ABCB1 by suppressing ERK and Akt [76].…”
Section: Sorcin Expression and Abcb1 Expression Are Linkedmentioning
confidence: 99%
“…Dihydromyricetin (DMY), a dihydroflavonol compound with anti-oxidant, anti-inflammatory, anti-bacterial, and anti-tumor effects, is able to reverse MDR in adriamycin-dependent MD-resistant breast cancer and leukemia cell lines and in a nude mice model, and to increase adriamycin cytotoxicity, by decreasing sorcin expression (both mRNA and protein), and consequently ABCB1 levels, via ERK/Akt pathways [24,76]. DMY increases intracellular free Ca 2+ concentration, reactive oxygen species (ROS) levels, and expression of caspase 12, i.e., markers of ER stress-linked apoptosis, and regulates expression of markers of mitochondrial apoptosis, such as caspase 9, caspase 3, Bcl-2, Bax, and PARP [24].…”
Section: Targeting Sorcinmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered expression of sorcin was found in the endometrium of women with mysterious infertility during the early-to-mid-secretory phase, suggesting a possible role of sorcin in endometrial receptivity and embryo implantation. Further, it was identified that sorcin regulates the Ca 2+ -dependent angiogenesis in endometrial cells via activating VEGF/PI3K/Akt pathway and prepares the endometrium for implantation [52] .…”
Section: Functions Of Sorcinmentioning
confidence: 99%
“…Sorcin increases proliferation, migration, and invasion in vitro in hepatocellular carcinoma and colorectal cancer cell, and facilitates cancer growth, metastasization and EMT, via activation of ERK and/or PI3K/Akt signaling pathways [79,97] . Sorcin is also involved in the regulation of Ca 2+ -mediated angiogenesis, via the VEGF/PI3K/Akt pathway in endometrial cells and plays a crucial role in preparing the endometrium for implantation [98] .…”
Section: Sri Overexpression In Md-resistant Cancers Sorcin Roles In mentioning
confidence: 99%